Increasing fidelity in lunar and martian analogs for behavioral health and performance research - Rahill, Katherine M.; Mulavara, Ajitkumar P.; George, Kerry; Gore, Brian F.; Whitmire, Alexandra M. (Frontiers in Space Technologies, 2025)
As the National Aeronautics and Space Administration (NASA), international space agencies, and commercial spaceflight programs set their sights on missions to the Moon and Mars, understanding the impact of spaceflight on astronauts’ health and performance becomes increasingly important. High-fidelity ground-based and space-based simulations of hazards induced by these missions can be used to conduct research that will help mitigate potential adverse outcomes in behavioral health and performance. In this review, current classifications of NASA’s research analogs are discussed, along with their strengths and limitations for effectively assessing risk to Moon- and Mars-bound astronauts’ behavioral health and performance. Recommendations are proposed for future consideration when designing high-fidelity analogs of spaceflight, which emphasize the importance of standardizing protocols, maintaining safety, and addressing ethical standards for future research and for developing analogs of mission-specific habitats.